Antenatal Care, Experiences and Views of Pregnant Women and their Health Care Providers in Duayaw-Nkwanta (2) - Gyameraa, D.N.A. (University of Ghana, 2018)
This study explored the experiences of pregnant women seeking facility-based antenatal care in Duayaw- Nkwanta and sought for the views of their health care providers. The objectives that guided the study were to explore the knowledge and perceptions of pregnant women and their health care providers in Duayaw-Nkwanta about antenatal care, ascertain the reasons why pregnant women seek antenatal care in Duayaw-Nkwanta, find out the challenges pregnant women and their health care providers face while providing or seeking antenatal care, and to find out what strategies pregnant women and their health care providers in Duayaw-Nkwanta adopt in coping with challenges. Using a qualitative research design, twenty-one pregnant women between the ages of 18 and 49 years seeking antenatal care in Duayaw-Nkwanta, five midwives and four TBAs/Herbalists in Duayaw-Nkwanta were recruited for this study. The findings of this study revealed that two types of antenatal care services that were accessed by some of the pregnant women at Duayaw- Nkwanta were the hospital based and the traditional based antenatal services. Majority of participants generally perceived antenatal care services to be beneficial to mother and baby. Some of the reasons pointed out by pregnant women seeking antenatal care at Duayaw-Nkwanta were to prevent health complications, their ability to ask questions and prayers. In addition, challenges encountered by some pregnant women seeking antenatal care as well as midwives and traditional birth attendants at Duayaw-Nkwanta were financial, facility based and spiritual challenges. Pregnant women seeking antenatal care expressed that in the midst of challenges, they resorted to getting a quiet place to rest, family support and prayers as ways to cope with challenges
MPhil.
Keywords: Antenatal Care; Health Care; Duayaw-Nkwanta